Trends of Professional Competencies on Guidance and Counseling Teachers: A Survey in Indonesia - Deasy Yunika Khairun; Agus Taufiq; Yusi Riksa Yustiana; Nandang Budiman; Ibrahim Al Hakim (STAI Hubbulwathan Duri, 2025)
Professional competencies are critical for guidance and counseling (GC) teachers to provide effective and accountable support services in educational settings. This study aimed to map the professional competency profiles of GC teachers and identify areas requiring enhancement. Data were collected from 93 GC teachers at public senior high schools in Bandung City, Indonesia, using a quantitative survey design. A validated questionnaire, based on national regulatory standards, was used to measure seven key aspects of professional competence, including assessment, program design, implementation, evaluation, supervision, personal development, and collaboration. The results indicated that 61% of participants demonstrated a medium level of competency, with only 20% reaching a high level. Teachers showed relative strength in theoretical knowledge and program planning but struggled in applying digital tools, conducting program evaluations, and supervising counselor trainees. Factors such as limited training, insufficient institutional support, and high counselor-to-student ratios were identified as contributing barriers. These findings highlight the need for targeted professional development programs that incorporate digital integration, collaborative models, and structured supervision frameworks. The study concludes that without systemic efforts to strengthen professional capacities, the effectiveness of school-based counseling services may remain limited. Further research is recommended to evaluate the impact of mentorship programs and technology-enhanced training models on long-term competency improvement among GC teachers.